2020
DOI: 10.3390/s20154188
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of Pd3-Modified Double-Vacancy Defect Graphene toward SF6 Decomposition Products

Abstract: In this study, we investigate Pd3-cluster-modified 555–777 graphene (Pd3-graphene) as a novel resistor-type gas sensor to detect SF6 decomposition products based on density functional theory calculations. We obtained and minutely analyzed the relevant parameters of each most stable adsorption configuration to explore the microscopic mechanism during gas adsorption. Theoretical results reveal that Pd3-graphene shows great adsorption capacity and sensitivity toward those decompositions. High adsorption energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Figure 1 b depicts the optimized configurations of three characteristic decomposition components of SF 6 . The bond length and bond angle of each gas molecule are marked in the figure, which is consistent with the literature [ 28 , 29 ].…”
Section: Resultssupporting
confidence: 87%
“…Figure 1 b depicts the optimized configurations of three characteristic decomposition components of SF 6 . The bond length and bond angle of each gas molecule are marked in the figure, which is consistent with the literature [ 28 , 29 ].…”
Section: Resultssupporting
confidence: 87%
“…Graphene materials have a unique single atomic layer structure and electronic band structure. Its excellent properties, such as high electron mobility, high thermal conductivity, and large specific surface area, make it an excellent candidate material for gas sensors [70][71][72][73]. Pd 3 doped with graphene (Pd 3 -graphene) can chemically adsorb H 2 S, SO 2 , SOF 2 , and SO 2 F 2 and has the best sensitivity to SOF 2 gas.…”
Section: D (Two-dimensional) Materials Sensor Materialsmentioning
confidence: 99%
“…Existing density functional theory studies on gas adsorption and sensing have demonstrated that introducing d-orbital electron activity through transition metal particle doping can enhance the intrinsic electron activity of the material, thereby achieving more ideal gas capture capabilities [ 9 , 29 , 30 ]. Furthermore, TM 3 clusters are considered the most stable small cluster doping structure and have been widely adopted to enhance various material properties [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%